VD_FINDINFO HC / 2014 / 155 vom 16. Januar 2014 - VD Tribunal cantonal (2014)
DIVORCE, OBLIGATION D'ENTRETIEN, LIQUIDATION DU RÉGIME MATRIMONIAL | 125 al. 1 CC, 125 al. 2 CC, 206 al. 1 CC, 209 al. 3 CC